ANATOMI DAN IDENTIFIKASI 21 JENIS KAYU KURANG DIKENAL - Y I Mandang (Jurnal Penelitian Hasil Hutan, 1991)
Grau and anatomical features of 21 leaer known wood species (10 families) were described and comJH11"814 There are 10 out of 21 species which have deco1Utiveappearances.i.e. Solenospermum javanicum, Luminitaera  littorea. Mutixia trichotoma,  Blumeodendron tokbrai,  Neoscbartechinia kingii, Pimeleodendron amboinicum,  Gymnostoma sumatranum, Wienmania blumei, Dillenia ex.celsaand Erythroxy Ion cuneatum.For identification purpo•• •veral  important features were noted. They  occur at least in one mt1mberof the follow- ing families: 1) veael  solitary  and radialy grouped in Caauarinaceae;.2) ueuel crou section are polygonal in Comaceae and Cunoniaceae; 3) intervet111elpit vestured in Combretaceae and Dipterocarpaceae; 4) Tylosis sclerotic in Euphorbiaceae;5) parenchyma banded or reticulate in Casuarinaceae, Celaateraceae, Cunoniaceae and Euphorbiaceae; 6) fiber storied in Datiscaceae; 7) 'fibers  uaually with  bordered pit at radial face in Erythrox.ylaceaeand Eupho:rbjaceae;8) vaacicentric bw1aflid in Casuarinaceae, Cunoniaceae and Dipterocarpaceae; 9) axial inter..celularcanal in Oomaeeae and Dipterocar- paceae; 1 O) raphide crystal in ray cells of Dilleniaceae;11) Disjunctive end wall in upright ray cells of Euphorbiaceae.Revision of  the formerly known  as Casuarina sumatrana Jungh. et de  Vriese into .Gymnostoma  sumatranum  L. A.S. Johnaon is BUJ)t)rted by anatomical charocters.